Antiglaucoma medication utilization and therapeutic outcome among Nigerian older persons with primary open angle glaucoma (Bangladesh Journal of Medical Science, 2019)
Background: Primary open angle glaucoma (POAG) is associated with older age. Antiglaucoma medications (AGM) are the cornerstones in the management of POAG. However, the relationship between AGM utilization, patients’ medication adherence (MA) and the therapeutic outcome remains largely unexplored among older persons.Objective: This study aimed to evaluate AGM utilization patterns, patients’ MA and intraocular pressure (IOP) reduction among older persons.Methods: This study was a 5-year retrospective review of medical records of consecutively selected older persons diagnosed of POAG at a University teaching hospital, in southwest Nigeria. Older persons were included if (1) aged 65 years and above, (2) had attended the outpatient ophthalmic clinics of the hospital between January 2010 and December 2015 (3) had at least 1-year clinic attendance during the period. The relationship between AGM utilization, patients’ self-reported MA and physicians’ comments on IOP was evaluated. A bivariate analysis was carried out to determine associations between variables and MA. Factors associated with IOP reduction were determined using a logistic regression. p